2013
DOI: 10.4172/2157-7412.1000203
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule Defects and Neurodegeneration

Abstract: One of the major challenges facing the long term survival of neurons is their requirement to maintain efficient axonal transport over long distances. In humans as large, long-lived vertebrates, the machinery maintaining neuronal transport must remain efficient despite the slow accumulation of cell damage during aging. Mutations in genes encoding proteins which function in the transport system feature prominently in neurologic disorders. Genes known to cause such disorders and showing traditional Mendelian inhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 49 publications
0
30
0
1
Order By: Relevance
“…Neurons are particularly vulnerable to dysfunction resulting from MT instability, because they rely on MT networks both for architectural support and for the axonal transport of critical cellular proteins and organelles (Alonso et al, 1997;Baird and Bennett, 2013). Thus, the loss of tau function would be predicted to be detrimental to MT function and neuronal health, as supported by the aforementioned observations in the AD brain.…”
Section: Discussionmentioning
confidence: 51%
“…Neurons are particularly vulnerable to dysfunction resulting from MT instability, because they rely on MT networks both for architectural support and for the axonal transport of critical cellular proteins and organelles (Alonso et al, 1997;Baird and Bennett, 2013). Thus, the loss of tau function would be predicted to be detrimental to MT function and neuronal health, as supported by the aforementioned observations in the AD brain.…”
Section: Discussionmentioning
confidence: 51%
“…Clinically relevant evidence for altered a-tubulin modifications in postmortem brain from patients with Alzheimer's [Zhang et al, 2015] Huntington's and Parkinson's disease [Perdiz et al, 2011] have also been reported, however the involvement of the microtubule cytoskeleton in the molecular mechanisms of neurodegenerative diseases has been extensively reviewed elsewhere [McMurray, 2000;Lingor et al, 2012;Baird and Bennett, 2013].…”
Section: Map6mentioning
confidence: 99%
“…In the brain, the protein tau is a member of microtubule‐associated proteins (MAPs) and its hyperphosphorylated form is a well‐established component of neurofibrillary tangles in AD (reviewed in ). A role for Tyr nitration was postulated in the formation of tau aggregates whereas a link between deamidation and isomerization of tau and the formation of aggregates has not been established although these PTMs have also been reported .…”
Section: Functional Classes Of Amyloid‐forming Proteinsmentioning
confidence: 99%